A glass fiber composite plastic product and a method for producing the same

CN122917531APending Publication Date: 2026-10-16CANGZHOU BOHAI NEW DISTRICT FENGYUANTAI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611175422.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,玻璃纤维与树脂基体之间的界面相容性是制约复合材料性能的关键因素,未经表面处理的玻璃纤维表面光滑、化学惰性强,与疏水性树脂基体的界面结合力薄弱,外力作用下纤维易从基体中拔出,无法充分发挥增强效应,现有技术中,将碳纳米管经多巴胺-氧化镧-碳化硅协同改性,并配合改性剂与玻璃纤维入增剂复配用于复合塑料制品的研究尚无报道

Benefits of technology

[0027]This invention constructs a multi-scale reinforcing network in composite plastic products through the synergistic compounding of a functional modifier and a glass fiber reinforcing agent. After synergistic modification with dopamine, lanthanum oxide, and silicon carbide, carbon nanotubes exhibit abundant surface-active functional groups and significantly improved dispersibility. Glass fibers, after grafting treatment, show a significantly enhanced interfacial bonding force with the resin matrix. The synergistic effect of these two agents simultaneously constructs a reinforcing network at both the nanoscale and microscale, significantly improving the mechanical properties, heat resistance, and weather resistance of the composite plastic products. In the functional modifier of this invention, dopamine hydrochloride self-polymerizes to form a polydopamine active layer, which... The subsequent loading of lanthanum oxide and silicon carbide provides a reaction platform. Lanthanum oxide, as a rare earth oxide, optimizes the interfacial chemical bonding, while silicon carbide whiskers provide micron-level reinforcement. The nano-reinforcement of nanocellulose, the flexibility and compatibilization of modified castor oil, and the synergistic effect of cinnamaldehyde in the modifier enable carbon nanotubes to achieve comprehensive functional modification. Glass fiber is incorporated into the additive, and the graft forms a chemical bond with the glass fiber surface, introducing active functional groups. The glass fiber treated with silane coupling agent forms a chemical bond with the polymer matrix, forming an interpenetrating network structure in the interfacial region, which significantly improves the interfacial bonding strength and thermal stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of high polymer composite materials, in particular to a glass fiber composite plastic product and a preparation method thereof. The composite plastic product comprises the following raw materials in parts by weight: a thermoplastic resin matrix 50-75 parts, a modified functional agent 3-10 parts, a glass fiber additive 15-35 parts and a processing aid 1-5 parts. Through the synergistic compounding of the modified functional agent and the glass fiber additive, the mechanical property, heat resistance and weathering stability of the composite plastic product are remarkably improved, and the composite plastic product is suitable for the fields of automobile parts, electronic and electrical appliance housings and building profiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plastic products technology, specifically to a glass fiber composite plastic product and its preparation method. Background Technology

[0002] Glass fiber reinforced plastics are widely used in the automotive, electronics, and building materials industries due to their excellent specific strength, corrosion resistance, and dimensional stability. Combining glass fibers with thermoplastic resins can significantly improve the tensile strength, flexural strength, and heat distortion temperature of the material. However, the interfacial compatibility between glass fibers and the resin matrix is ​​a key factor limiting the performance of composite materials. Untreated glass fibers have smooth surfaces and strong chemical inertness, resulting in weak interfacial bonding with hydrophobic resin matrices. Under external forces, the fibers are easily pulled out of the matrix, failing to fully realize the reinforcing effect. Currently, there are no reports on the use of carbon nanotubes synergistically modified with dopamine-lanthanum oxide-silicon carbide, combined with modifiers and glass fibers as reinforcing agents, for composite plastic products. Summary of the Invention

[0003] In view of the deficiencies of the prior art, the purpose of this invention is to provide a glass fiber composite plastic product and its preparation method, so as to solve the problems mentioned in the background art.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] This invention provides a glass fiber composite plastic product comprising the following raw materials in parts by weight: 50-75 parts of thermoplastic resin matrix, 3-10 parts of modified functional agent, 15-35 parts of glass fiber additive, and 1-5 parts of processing aid.

[0006] Preferably, the thermoplastic resin matrix is ​​at least one of polyamide, polycarbonate, polyoxymethylene, polyphenylene sulfide, or acrylonitrile-butadiene-styrene copolymer. Different resin matrices can be selected according to the performance requirements of the target product. Polyamide has excellent mechanical properties and heat resistance, polycarbonate has high transparency and impact toughness, and polyoxymethylene has high rigidity and fatigue resistance.

[0007] Preferably, the method for preparing the modified functional agent is as follows:

[0008] S11: Carbon nanotubes are added to a dopamine hydrochloride solution with a mass fraction of 0.5% to 2% and a pH value of 8.0 to 9.0. The mixture is stirred at 25 to 40°C for 12 to 24 hours to obtain dopamine-modified carbon nanotubes.

[0009] Dopamine hydrochloride undergoes oxidative self-polymerization under weakly alkaline conditions, forming a polydopamine coating layer on the surface of carbon nanotubes and introducing catechol and amine active functional groups.

[0010] S12: Lanthanum oxide and silicon carbide are added to dopamine-modified carbon nanotubes. The weight ratio of lanthanum oxide to carbon nanotubes is 1:0.2 to 1:0.5, and the weight ratio of silicon carbide to carbon nanotubes is 1:0.3 to 1:0.8. The mixture is stirred at 300 to 500 r / min for 2 to 4 hours at 50 to 80 °C to obtain composite carbon nanotubes.

[0011] Lanthanum oxide binds to the catechol groups of the polydopamine layer through coordination, and silicon carbide whiskers are combined with carbon nanotubes through physical mixing and chemical bonding.

[0012] S13: Add a modifier to the composite carbon nanotubes. The weight ratio of the modifier to the carbon nanotubes is 1:0.1 to 1:0.3. Continue stirring and reacting for 1 to 3 hours. After filtration, washing, and drying at 80 to 120°C, the modified functional agent is obtained.

[0013] Preferably, the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10–50 nm and a length of 5–30 μm; the lanthanum oxide particles have a diameter of 10–100 nm; and the silicon carbide whiskers have a diameter of 0.5–3 μm and an aspect ratio of 10:1–50:1.

[0014] Preferably, the modifier is prepared by mixing nanocellulose, modified castor oil and cinnamaldehyde in a weight ratio of 1:0.3-0.8:0.2-0.6, stirring at 300-500 r / min for 2-5 hours at 40-70°C, and then drying and grinding to obtain the modifier.

[0015] Nanocellulose has a high aspect ratio and high mechanical strength, and can form a nano-reinforcing network on the surface of carbon nanotubes. Modified castor oil, as a natural oil derivative, contains active functional groups, which can enhance the compatibility and flexibility between the components. Cinnamaldehyde itself has good antibacterial and antioxidant properties, which helps to improve the weather resistance stability of the composite material.

[0016] Preferably, the nanocellulose is cellulose nanocrystals or cellulose nanofibers with a diameter of 5-50 nm and a length of 100-500 nm; the modified castor oil is epoxy-modified castor oil or maleic anhydride-modified castor oil.

[0017] Preferably, the glass fiber additive is prepared by adding glass fiber to the graft body solution, wherein the weight ratio of glass fiber to graft body is 1:0.05 to 1:0.15, stirring and reacting at 300 to 500 r / min at 60 to 90°C for 2 to 5 hours, and then filtering, washing, and drying at 80 to 120°C to obtain the glass fiber additive.

[0018] Grafts form chemical bonds on the surface of glass fibers, introducing active functional groups compatible with the resin matrix. The adhesion between grafted glass fibers and the resin matrix is ​​significantly enhanced, effectively improving the mechanical properties and thermal stability of the composite material.

[0019] Preferably, the glass fiber is chopped glass fiber or continuous glass fiber with a diameter of 5-20 μm and a length of 3-30 mm; the graft is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane or maleic anhydride grafted polypropylene.

[0020] Preferably, the processing aid is at least one of an antioxidant, a lubricant, or a coupling agent.

[0021] This invention also provides a method for preparing glass fiber composite plastic products, comprising the following steps:

[0022] S01. Mixing: The thermoplastic resin matrix, modified functional agent, glass fiber additive and processing aid are added into a high-speed mixer according to the proportion and mixed at 500-1000 r / min for 10-30 minutes to obtain a mixture.

[0023] S02, Melt Blending: The mixture is fed into a twin-screw extruder for melt blending. The extrusion temperature is 200-300℃ and the screw speed is 200-400 r / min. After extrusion, cooling, and pelletizing, composite particles are obtained.

[0024] S03, Injection Molding: The composite granules are fed into an injection molding machine and injection molded to obtain glass fiber composite plastic products.

[0025] Preferably, the extrusion temperature of the twin-screw extruder in S02 is: 200-230°C in the feeding section, 230-260°C in the melting section, 260-290°C in the homogenization section, and 270-300°C in the die head; the mold temperature of the injection molding in S03 is 60-120°C, and the injection pressure is 60-150 MPa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] This invention constructs a multi-scale reinforcing network in composite plastic products through the synergistic compounding of a functional modifier and a glass fiber reinforcing agent. After synergistic modification with dopamine, lanthanum oxide, and silicon carbide, carbon nanotubes exhibit abundant surface-active functional groups and significantly improved dispersibility. Glass fibers, after grafting treatment, show a significantly enhanced interfacial bonding force with the resin matrix. The synergistic effect of these two agents simultaneously constructs a reinforcing network at both the nanoscale and microscale, significantly improving the mechanical properties, heat resistance, and weather resistance of the composite plastic products. In the functional modifier of this invention, dopamine hydrochloride self-polymerizes to form a polydopamine active layer, which... The subsequent loading of lanthanum oxide and silicon carbide provides a reaction platform. Lanthanum oxide, as a rare earth oxide, optimizes the interfacial chemical bonding, while silicon carbide whiskers provide micron-level reinforcement. The nano-reinforcement of nanocellulose, the flexibility and compatibilization of modified castor oil, and the synergistic effect of cinnamaldehyde in the modifier enable carbon nanotubes to achieve comprehensive functional modification. Glass fiber is incorporated into the additive, and the graft forms a chemical bond with the glass fiber surface, introducing active functional groups. The glass fiber treated with silane coupling agent forms a chemical bond with the polymer matrix, forming an interpenetrating network structure in the interfacial region, which significantly improves the interfacial bonding strength and thermal stability. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] This embodiment of a glass fiber composite plastic product includes the following raw materials in parts by weight: 50-75 parts of thermoplastic resin matrix, 3-10 parts of modified functional agent, 15-35 parts of glass fiber additive, and 1-5 parts of processing aid.

[0030] The thermoplastic resin matrix in this embodiment is at least one of polyamide, polycarbonate, polyoxymethylene, polyphenylene sulfide, or acrylonitrile-butadiene-styrene copolymer.

[0031] The preparation method of the modified functional agent in this embodiment is as follows:

[0032] S11: Carbon nanotubes are added to a dopamine hydrochloride solution with a mass fraction of 0.5% to 2% and a pH value of 8.0 to 9.0. The mixture is stirred at 25 to 40°C for 12 to 24 hours to obtain dopamine-modified carbon nanotubes.

[0033] S12: Lanthanum oxide and silicon carbide are added to dopamine-modified carbon nanotubes. The weight ratio of lanthanum oxide to carbon nanotubes is 1:0.2 to 1:0.5, and the weight ratio of silicon carbide to carbon nanotubes is 1:0.3 to 1:0.8. The mixture is stirred at 300 to 500 r / min for 2 to 4 hours at 50 to 80 °C to obtain composite carbon nanotubes.

[0034] S13: Add a modifier to the composite carbon nanotubes. The weight ratio of the modifier to the carbon nanotubes is 1:0.1 to 1:0.3. Continue stirring and reacting for 1 to 3 hours. After filtration, washing, and drying at 80 to 120°C, the modified functional agent is obtained.

[0035] The carbon nanotubes in this embodiment are multi-walled carbon nanotubes with a diameter of 10–50 nm and a length of 5–30 μm; the lanthanum oxide particles have a diameter of 10–100 nm; and the silicon carbide whiskers have a diameter of 0.5–3 μm and an aspect ratio of 10:1–50:1.

[0036] The modifier in this embodiment is prepared by mixing nanocellulose, modified castor oil and cinnamaldehyde in a weight ratio of 1:0.3-0.8:0.2-0.6, stirring at 300-500 r / min for 2-5 hours at 40-70°C, and then drying and grinding to obtain the modifier.

[0037] In this embodiment, the nanocellulose is cellulose nanocrystals or cellulose nanofibers with a diameter of 5-50 nm and a length of 100-500 nm; the modified castor oil is epoxy-modified castor oil or maleic anhydride-modified castor oil.

[0038] The preparation method of the glass fiber additive in this embodiment is as follows: glass fiber is added to the graft body solution, the weight ratio of glass fiber to graft body is 1:0.05 to 1:0.15, and the mixture is stirred at 300 to 500 r / min at 60 to 90°C for 2 to 5 hours. After filtration, washing, and drying at 80 to 120°C, the glass fiber additive is obtained.

[0039] In this embodiment, the glass fiber is chopped glass fiber or continuous glass fiber with a diameter of 5-20 μm and a length of 3-30 mm; the graft is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane or maleic anhydride grafted polypropylene.

[0040] The processing aid in this embodiment is at least one of antioxidants, lubricants, or coupling agents.

[0041] The method for preparing the glass fiber composite plastic product in this embodiment includes the following steps:

[0042] S01. Mixing: The thermoplastic resin matrix, modified functional agent, glass fiber additive and processing aid are added into a high-speed mixer according to the proportion and mixed at 500-1000 r / min for 10-30 minutes to obtain a mixture.

[0043] S02, Melt Blending: The mixture is fed into a twin-screw extruder for melt blending. The extrusion temperature is 200-300℃ and the screw speed is 200-400 r / min. After extrusion, cooling, and pelletizing, composite particles are obtained.

[0044] S03, Injection Molding: The composite granules are fed into an injection molding machine and injection molded to obtain glass fiber composite plastic products;

[0045] The extrusion temperature of the twin-screw extruder described in S02 is: 200-230℃ in the feeding section, 230-260℃ in the melting section, 260-290℃ in the homogenization section, and 270-300℃ in the die head; the mold temperature of the injection molding described in S03 is 60-120℃, and the injection pressure is 60-150MPa.

[0046] Example 1

[0047] A glass fiber composite plastic product comprises the following raw materials in parts by weight: 62 parts of polyamide 66 resin, 5 parts of modified functional agent, 28 parts of glass fiber additive, 0.5 parts of antioxidant 1010, 1.5 parts of lubricant, and 1 part of coupling agent.

[0048] Preparation of modified functional agents:

[0049] S11: Add multi-walled carbon nanotubes with a diameter of 25 nm and a length of 15 μm to a 1% (w / w) solution of dopamine hydrochloride at pH 8.5, and stir at 30 °C for 18 hours to obtain dopamine-modified carbon nanotubes.

[0050] S12: Lanthanum oxide with a particle size of 50 nm and silicon carbide whiskers with a diameter of 1.5 μm and an aspect ratio of 30:1 were added to dopamine-modified carbon nanotubes. The weight ratio of lanthanum oxide to carbon nanotubes was 1:0.35, and the weight ratio of silicon carbide to carbon nanotubes was 1:0.5. The mixture was stirred at 400 r / min at 65 °C for 3 hours to obtain composite carbon nanotubes.

[0051] S13: Preparation of the modifier: 20 nm diameter and 300 nm length cellulose nanofibers, epoxy modified castor oil and cinnamaldehyde were mixed in a weight ratio of 1:0.5:0.4 and stirred at 400 r / min for 3 hours at 60 °C. After drying and grinding, the modifier was obtained.

[0052] S14: Add a modifier to the composite carbon nanotubes at a weight ratio of 1:0.2, continue stirring for 2 hours, filter, wash with deionized water, and dry at 105℃ to obtain the modified functional agent.

[0053] Preparation of glass fiber grafting agent: Short glass fibers with a diameter of 13 μm and a length of 6 mm were added to a γ-aminopropyltriethoxysilane solution. The weight ratio of glass fiber to graft was 1:0.1. The mixture was stirred at 400 r / min for 3 hours at 75 °C. After filtration, washing with ethanol, and drying at 100 °C, the glass fiber grafting agent was obtained.

[0054] Preparation method:

[0055] S01. Mixing: Add polyamide 66 resin, modified functional agent, glass fiber additive, antioxidant, lubricant and coupling agent into a high-speed mixer according to the proportion, and mix at 800 r / min for 20 minutes to obtain a mixture.

[0056] S02, Melt Blending: The mixture is fed into a twin-screw extruder for melt blending. The extrusion temperature is 220°C in the feeding section, 250°C in the melting section, 275°C in the homogenization section, and 285°C in the die head. The screw speed is 300 r / min. After extrusion, cooling, and pelletizing, composite particles are obtained.

[0057] S03. Injection Molding: The composite granules are fed into the injection molding machine. The mold temperature is 80℃ and the injection pressure is 100MPa. After injection molding, glass fiber composite plastic products are obtained.

[0058] Example 2

[0059] A glass fiber composite plastic product comprises the following raw materials in parts by weight: 58 parts polycarbonate, 7 parts modified functional agent, 30 parts glass fiber additive, 0.5 parts antioxidant 1076, 2 parts lubricant, and 0.5 parts coupling agent.

[0060] In the preparation of the modified functional agent, the carbon nanotubes had a diameter of 30 nm and a length of 10 μm. The dopamine hydrochloride solution had a mass fraction of 1.5% and a pH of 8.8. The reaction temperature was 35 °C and the reaction time was 20 h. The weight ratio of lanthanum oxide to carbon nanotubes was 1:0.4, and the weight ratio of silicon carbide to carbon nanotubes was 1:0.6. The weight ratio of nanocellulose, modified castor oil, and cinnamaldehyde in the modifier was 1:0.6:0.5. The remaining conditions were the same as in Example 1.

[0061] In the preparation of glass fiber as a grafting agent, the glass fiber has a diameter of 10 μm and a length of 4.5 mm. The grafting agent is γ-glycidyl etheroxypropyltrimethoxysilane. The weight ratio of glass fiber to grafting agent is 1:0.08. The reaction temperature is 80℃ and the reaction time is 2.5 h.

[0062] The extrusion temperatures in the preparation method are as follows: feeding section 230℃, melting section 260℃, homogenization section 280℃, die head temperature 290℃, and mold temperature 100℃. The rest is the same as in Example 1.

[0063] Example 3

[0064] A glass fiber composite plastic product comprises the following raw materials in parts by weight: 55 parts polyphenylene sulfide, 6 parts modified functional agent, 35 parts glass fiber additive, 0.3 parts antioxidant 1010, 1.5 parts lubricant, and 0.7 parts coupling agent.

[0065] In the preparation of the modified functional agent, the carbon nanotubes had a diameter of 20 nm and a length of 20 μm. The dopamine hydrochloride solution had a mass fraction of 0.8% and a pH of 8.2. The reaction temperature was 28 °C and the reaction time was 22 h. The weight ratio of lanthanum oxide to carbon nanotubes was 1:0.3, and the weight ratio of silicon carbide to carbon nanotubes was 1:0.7. The weight ratio of nanocellulose, modified castor oil, and cinnamaldehyde in the modifier was 1:0.4:0.3. The remaining conditions were the same as in Example 1.

[0066] In the preparation of glass fiber additive, the glass fiber has a diameter of 14μm and a length of 3mm. The graft is maleic anhydride grafted polypropylene. The weight ratio of glass fiber to graft is 1:0.12. The reaction temperature is 85℃ and the time is 2h.

[0067] The extrusion temperatures in the preparation method are as follows: feeding section 235℃, melting section 265℃, homogenization section 285℃, die head temperature 295℃, and mold temperature 110℃. The rest are the same as in Example 1.

[0068] Scaling settings,

[0069] Comparative Example 1: Unlike Example 1, no modifying functional agent was added; only glass fiber additive was used to composite the resin matrix.

[0070] Comparative Example 2: Unlike Example 1, no glass fiber additive was added; instead, a functional modifier was used to composite the resin matrix.

[0071] Comparative Example 3: Unlike Example 1, dopamine hydrochloride was not added during the preparation of the modified functional agent, and carbon nanotubes were directly combined with lanthanum oxide and silicon carbide.

[0072] Comparative Example 4: Unlike Example 1, lanthanum oxide was not added in the preparation of the modified functional agent, and the carbon nanotubes were only modified with dopamine and composited with silicon carbide.

[0073] Comparative Example 5: Unlike Example 1, in the preparation of the glass fiber additive, the glass fiber was not treated with grafting agent and was directly compounded with the resin matrix.

[0074] Performance testing

[0075] The composite plastic products prepared in Examples 1-3 and Comparative Examples 1-5 were tested for tensile strength, flexural strength, heat distortion temperature and strength retention rate after ultraviolet aging.

[0076] Tensile strength and flexural strength tests shall be conducted in accordance with GB / T 1040 and GB / T 9341 standards.

[0077] The heat distortion temperature was tested in accordance with GB / T 1634 standard and measured under a load of 1.82 MPa.

[0078] Weathering test: The sample was placed in an ultraviolet aging chamber with a UVA-340 lamp, an irradiance of 0.89 W / m²·nm, a black panel temperature of 60℃, and an aging time of 168 hours. The tensile strength retention rate after aging was then tested.

[0079] Table 1 Performance test results of composite plastic products

[0080] Group Tensile strength / MPa Bending strength / MPa Heat distortion temperature / ℃ Strength retention rate after UV aging / % Example 1 135.2 198.5 245.6 91.5 Example 2 128.6 185.3 238.2 90.8 Example 3 142.8 205.6 252.3 92.3 Comparative Example 1 98.5 152.6 212.5 78.6 Comparative Example 2 82.3 118.5 195.8 85.2 Comparative Example 3 112.6 168.5 225.6 82.5 Comparative Example 4 118.5 172.3 228.5 83.8 Comparative Example 5 105.8 158.2 218.6 80.2

[0081] As shown in Table 1, the composite plastic products prepared in Examples 1-3 have tensile strength of 128.6-142.8 MPa, flexural strength of 185.3-205.6 MPa, heat distortion temperature of 238.2-252.3℃, and strength retention rate after ultraviolet aging of 90.8%-92.3%, demonstrating excellent comprehensive performance.

[0082] Comparative Example 1, without the addition of the modified functional agent, had a tensile strength of only 98.5 MPa, a heat distortion temperature of 212.5℃, and a strength retention rate of only 78.6% after UV aging. This demonstrates that the addition of the modified functional agent plays a crucial role in improving the mechanical properties and heat and weather resistance of the composite material.

[0083] Comparative Example 2, without the addition of glass fiber additive, had a tensile strength of only 82.3 MPa and a heat distortion temperature of 195.8℃, proving that the glass fiber additive is the main load-bearing skeleton of the composite material.

[0084] In Comparative Example 3, the carbon nanotubes in the modified functional agent were not modified with dopamine hydrochloride, resulting in insufficient interfacial bonding and decreased mechanical and weather resistance properties. This demonstrates that dopamine hydrochloride modification plays a crucial role in constructing the surface active layer of carbon nanotubes.

[0085] In Comparative Example 4, no lanthanum oxide was added to the modified functional agent, resulting in a lack of rare earth interface optimization effect and lower performance than the examples. This demonstrates that lanthanum oxide plays an important role in optimizing the interfacial bonding between carbon nanotubes and the matrix.

[0086] Comparative Example 5: The glass fiber without graft treatment had weak interfacial bonding, and its mechanical properties and weather resistance were reduced. This proves that graft treatment plays an indispensable role in improving the interfacial compatibility between glass fiber and resin matrix.

[0087] This invention constructs a multi-scale reinforcing network in composite plastic products through the synergistic compounding of functional modifiers and glass fiber reinforcing agents. Carbon nanotubes, after synergistic modification with dopamine-lanthanum oxide-silicon carbide and modification with nanocellulose-modified castor oil-cinnamaldehyde modifiers, exhibit high surface functionalization and excellent dispersibility. Glass fibers, after grafting treatment, achieve a strong interfacial bond with the resin matrix. The synergistic effect of these two factors comprehensively improves the mechanical properties, heat resistance, and weather resistance of the composite material.

[0088] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0089] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A glass fiber composite plastic product, characterized in that, It includes the following raw materials in parts by weight: 50-75 parts thermoplastic resin matrix, 3-10 parts modified functional agent, 15-35 parts glass fiber additive, and 1-5 parts processing aid.

2. The glass fiber composite plastic product according to claim 1, characterized in that, The thermoplastic resin matrix is ​​at least one of polyamide, polycarbonate, polyoxymethylene, polyphenylene sulfide, or acrylonitrile-butadiene-styrene copolymer.

3. The glass fiber composite plastic product according to claim 1, characterized in that, The preparation method of the modified functional agent is as follows: S11: Carbon nanotubes are added to a dopamine hydrochloride solution with a mass fraction of 0.5% to 2% and a pH value of 8.0 to 9.

0. The mixture is stirred at 25 to 40°C for 12 to 24 hours to obtain dopamine-modified carbon nanotubes. S12: Lanthanum oxide and silicon carbide are added to dopamine-modified carbon nanotubes. The weight ratio of lanthanum oxide to carbon nanotubes is 1:0.2 to 1:0.5, and the weight ratio of silicon carbide to carbon nanotubes is 1:0.3 to 1:0.

8. The mixture is stirred at 300 to 500 r / min for 2 to 4 hours at 50 to 80 °C to obtain composite carbon nanotubes. S13: Add a modifier to the composite carbon nanotubes. The weight ratio of the modifier to the carbon nanotubes is 1:0.1 to 1:0.

3. Continue stirring and reacting for 1 to 3 hours. After filtration, washing, and drying at 80 to 120°C, the modified functional agent is obtained.

4. The glass fiber composite plastic product according to claim 3, characterized in that, The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10–50 nm and a length of 5–30 μm; the lanthanum oxide particles have a diameter of 10–100 nm; and the silicon carbide whiskers have a diameter of 0.5–3 μm and an aspect ratio of 10:1–50:

1.

5. The glass fiber composite plastic product according to claim 3, characterized in that, The modifier is prepared by mixing nanocellulose, modified castor oil and cinnamaldehyde in a weight ratio of 1:0.3-0.8:0.2-0.6, stirring at 300-500 r / min for 2-5 hours at 40-70℃, and then drying and grinding to obtain the modifier.

6. The glass fiber composite plastic product according to claim 5, characterized in that, The nanocellulose is cellulose nanocrystals or cellulose nanofibers with a diameter of 5-50 nm and a length of 100-500 nm; the modified castor oil is epoxy-modified castor oil or maleic anhydride-modified castor oil.

7. The glass fiber composite plastic product according to claim 1, characterized in that, The glass fiber additive is prepared by adding glass fiber to the graft body solution, wherein the weight ratio of glass fiber to graft body is 1:0.05 to 1:0.15, stirring at 300 to 500 r / min for 2 to 5 hours at 60 to 90°C, and then filtering, washing, and drying at 80 to 120°C to obtain the glass fiber additive.

8. The glass fiber composite plastic product according to claim 7, characterized in that, The glass fiber is chopped glass fiber or continuous glass fiber, with a diameter of 5-20 μm and a length of 3-30 mm; the graft is at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, or maleic anhydride-grafted polypropylene.

9. The glass fiber composite plastic product according to claim 1, characterized in that, The processing aid is at least one of antioxidants, lubricants, or coupling agents.

10. A method for preparing a glass fiber composite plastic article as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S01. Mixing: The thermoplastic resin matrix, modified functional agent, glass fiber additive and processing aid are added into a high-speed mixer according to the proportion and mixed at 500-1000 r / min for 10-30 minutes to obtain a mixture. S02, Melt Blending: The mixture is fed into a twin-screw extruder for melt blending. The extrusion temperature is 200-300℃ and the screw speed is 200-400 r / min. After extrusion, cooling, and pelletizing, composite particles are obtained. S03, Injection Molding: The composite granules are fed into an injection molding machine and injection molded to obtain glass fiber composite plastic products; The extrusion temperature of the twin-screw extruder described in S02 is: 200-230℃ in the feeding section, 230-260℃ in the melting section, 260-290℃ in the homogenization section, and 270-300℃ in the die head; the mold temperature of the injection molding described in S03 is 60-120℃, and the injection pressure is 60-150MPa.